The impact of verbal encouragement during the repeated agility speed training on internal intensity, mood state, and physical enjoyment in youth soccer players - Selmi, Okba; Jelleli, Hilmi; Bouali, Souheir; Aydi, Bilel; Hindawi, Omar; Muscella, Antonella; Bouassida, Anissa; Weiss, Katja; Knechtle, Beat (Frontiers in Psychology, 2023)
Objective Verbal encouragement (VE) can be used by coaches to boost morale and commitment during training exercises. This investigation aimed to study the impacts of VE given by coaches on the physiological aspects, players' internal intensity, mood, and perceived enjoyment of youth soccer players during repeated agility speed training (RAS). Methods A total of 17 male youth soccer players (mean ± SD; age: 13.8 ± 0.4 years; body mass: 59.1 ± 6.7 kg; height: 170.0 ± 6.2 cm; training experience: 5.1 ± 0.7 years) participated, in a randomized order, in two experimental training sessions that consisted of a RAS (i.e., the Illinois course) either with VE (RAS-E) or without VE (RAS-NE), with a 7-day interval between the testing sessions. Heart rate (HR) was registered throughout the exercise. The rating of perceived exertion, blood lactate concentration [La], and perceived enjoyment were measured after each training session. The mood state was recorded before and after each protocol. Results HR mean (Cohen's coefficient d = 0.45, small), %HRmax (d = 0.37, small), HR peak (d = 0.66, moderate), [La] (d = 0.56, small), and the PACES score (d = 2.8, very large) were higher in RAS-E compared to RAS-NE (all, P < 0.001). Compared to the RAS-E trial, the RAS-NE trial showed higher fatigue (P < 0.01), tension (P < 0.05), anger (0.05), total mood score (P < 0.001), and lower vigor (P < 0.001). Conclusion Coaches may use VE during RAS to improve psychophysiological responses, mood state, and perceived enjoyment in youth soccer players.